Conceptualizing Motherhood in Yoga: Pregnancy-Oriented Iyengar Yoga - Wittich, Agi (Religions of South Asia, 2024)
Prenatal yoga classes have become widespread worldwide. Still, while scientific studies examined the benefits of such practices, the conceptual and sociocultural meanings still need to be studied. This paper focuses on pregnancy-oriented Iyengar yoga, which includes pre-conception, prenatal and postnatal yoga practices developed in the Iyengar Yoga school. Interestingly, while these practices are seen as ideal for pregnant and postpartum women, they contrast with what is perceived as an ideal yoga practice. Thus, pregnancy-oriented Iyengar Yoga reveals a shift in purpose from achieving an excellent and advanced yoga practice to the health of female yoga practitioners and their children in a modern lifestyle setting. The findings of this paper are based on my doctoral research, and draw on textual analysis of over fifty relevant Iyengar yoga publications, and qualitative interviews with thirty-seven Iyengar Yoga teachers and four members of the Iyengar family between 2015 and 2019.